On-line head loss identification for monitoring of pipelines⁎. Issue 24 (2018) - Rojas, J.; Verde, C.; Torres, L.; Pérez, E.
Abstract: This paper presents an approach based on state observers to identify on-line the parameters associated with frictional head loss in pressurized pipelines. A characteristic of the approach is that it allows the parameters' identification for any line or branch of a network. In particular, two smooth approximations for the friction are considered: a linear and a nonlinear function. These functions depend on the flow rate and two coefficients, which are identified without assuming that either the pipeline roughness nor the Reynolds number are known. Hence, the approach can be used on-line to supervise the status of a pipeline section throughout its useful life and not only during the design and maintenance stages. The simplicity and performance of the approach is shown by considering real data of two water pipelines with different physical characteristics.